2009
DOI: 10.1002/dvg.20511
|View full text |Cite
|
Sign up to set email alerts
|

Bmp2 and Bmp4 genetically interact to support multiple aspects of mouse development including functional heart development

Abstract: Summary Bone morphogenetic proteins (BMPs) have multiple roles during embryogenesis. Current data indicate that the dosage of BMPs is tightly regulated for normal development in mice. Since Bmp2 or Bmp4 homozygous mutant mice show early embryonic lethality, we generated compound heterozygous mice for Bmp2 and Bmp4 to explore the impact of lowered dosage of these BMP ligands. Genotyping pups bred between Bmp2 and Bmp4 heterozygous mice revealed that the ratio of adult compound heterozygous mice for Bmp2 and Bmp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 55 publications
2
46
0
Order By: Relevance
“…Several studies revealed that there was interaction between BMP2 and BMP4. 16,17 We found that BMP4 treatment did not affect BMP2 protein expression in cardiomyocytes ( Figure S11C). …”
Section: Bmp4 Induces Cardiomyocyte Hypertrophy and Apoptosis Throughmentioning
confidence: 92%
“…Several studies revealed that there was interaction between BMP2 and BMP4. 16,17 We found that BMP4 treatment did not affect BMP2 protein expression in cardiomyocytes ( Figure S11C). …”
Section: Bmp4 Induces Cardiomyocyte Hypertrophy and Apoptosis Throughmentioning
confidence: 92%
“…40 Both genes are highly conserved, with over 90% similarity in mature proteins. 41 There is also a possible biological explanation for height in infants/children in early childhood by PTPN7. PTPN7 is a member of the PTP family.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar work, it has been observed that ECs are also involved during the early stages of pancreas development [20] . Another research work indicated that signals from myocardium, such as those exerted by bone morphogenetic protein-2 (BMP-2), can promote epithelial-mesenchymal transformation mediated by ECs [24,29] . In the kidney, VEGF, bFGF, and PDGF coordinate cellular differentiation, proliferation, and migration [30] .…”
Section: Endothelium As An Endocrine Organmentioning
confidence: 99%